Learning History from Patent Medicines: Newbro’s Herpicide in Early Twentieth Century Kansas - Wolf, Natalie (Kansas State University. Dept. of History, 2018)
The material culture research project "Learning History from Patent Medicines: Newbro's Herpicide in Early Twentieth Century Kansas" explores the history of Newbro’s Herpicide, a product designed to kill the “dandruff germ,” in the early twentieth century through its connections to hair culture, patent medicines, and newspaper advertisements, particularly focusing on its presence in Kansas. It does so by first examining the prevailing characteristics associated with healthy hair in the early twentieth century in the United States for both men (virility) and women (beauty). It then moves specifically to the subject of dandruff, first exploring some practices of the day that could have helped contribute to the condition (tall hairstyles, products such as pomade, infrequent bathing) before taking a look at the medical opinions of the time regarding the causes of dandruff and baldness, and the apparent discovery of a “dandruff germ” that could be linked to both conditions. This project then looks into how the patent medicine Herpicide, claiming to kill this “dandruff germ” was created and began to spread like wildfire, especially within Kansas, as seen through its significant presence in local newspaper advertisements. Finally, this project then concludes by discussing the eventual decline of herpicide, due to such possible reasons as increased federal regulation regarding pharmaceuticals and the rise of shorter hairstyles among women, and its lasting impact on American popular culture. The project is overall based on a bottle of Newbro’s Herpicide found at the Clay County Museum and Historical Society. It uses newspaper ads for Herpicide as its foundational primary source while also employing a number of other primary and secondary sources on subjects such as medical journals, histories of hair and hat styles within the U.S., and contemporary short fiction.
Kirmser Undergraduate Research Award - Individual Non-Freshman category, honorable mention
Keywords: Newbro's Herpicide; Hair Culture; Patent Medicine; Newspaper Advertisements; Kansas; Early 20th Century